2018
DOI: 10.7150/jca.24934
|View full text |Cite
|
Sign up to set email alerts
|

P21-activated kinase 7 (PAK7) interacts with and activates Wnt/β-catenin signaling pathway in breast cancer

Abstract: Background: Breast cancer is the highest incidence of tumor in women, which seriously threaten women's health. The occurrence and progression of breast cancer is linked to inactivation or downregulation of tumor suppressors, and activation or upregulation of oncogenes. However, the mechanism of PAK7 involving in the occurrence and progression of breast cancer is not yet fully understood.Methods: PAK7 expression was analyzed by RT-qPCR and immunohistochemistry and correlated with clinicopatholgical parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…We also quantified the percentage of wound healing via image processing (Figure B). Previous studies consistently reported that, in the same cell populations, mesenchymal phenotypes have a higher rate of migration and fill the scratch in a shorter time when compared to epithelial phenotypes. , …”
Section: Resultsmentioning
confidence: 82%
“…We also quantified the percentage of wound healing via image processing (Figure B). Previous studies consistently reported that, in the same cell populations, mesenchymal phenotypes have a higher rate of migration and fill the scratch in a shorter time when compared to epithelial phenotypes. , …”
Section: Resultsmentioning
confidence: 82%
“…The results of the CCK‐8 assay showed that overexpression of GMDS‐AS1 significantly inhibited the proliferation of cells (Figure G,H), which were consistent with the results of colony formation assay (Figure I,J). Cyclin A1 and cyclin B1 belong to the cyclin family, which accelerate the cell cycle by interacting with cyclin‐dependent kinases (CDKs) . Therefore, upregulation of cyclin A1 and cyclin B1 expression levels can promote cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The TOP/FOP flash assay is a reporter gene assay used to detect Wnt/β‐catenin signaling pathway activity . The TOP flash reporter plasmid contains a wild‐type (CCTTTGATC) TCF/LEF binding site, and the FOP flash reporter plasmid contains a muted (CCTTTGGCC) TCF/LEF binding site.…”
Section: Methodsmentioning
confidence: 99%